Multi Agent Systems Combined with Semantic Technologies for Automated Negotiation in Virtual Enterprises - Gottfried, Koppensteiner; Munir, Merdan; Wilfried, Lepuschitz; Thomas, Moser; Constantin, Reinprecht (IntechOpen, 2011)
None